Effect of water inflows on the strength characteristics of the Lovozero rare-metal deposit rocks - Anatoly I. Kalashnik (Горные науки и технологии)
The Lovozero rare-metal deposit is represented by a series of sheet-like ore bodies of small and medium thickness exposing on the northwestern slopes of the Lovozero massif. The purpose of the work is to assess the impact of water inflows on the strength characteristics of the rocks of the Lovozero rare-metal deposit developed by the Karnasurt mine. The data on water inflow into Karnasurt mine workings, which exploits two ore bodies of the Lovozero rare-metal deposit, are considered. Statistical processing of the data on water volumes collected by the mine over the latest 4 years was performed, with assessment of their changes during a calendar year. The peculiarities associated with calendar climatic changes were identified. The main purpose of the study was to assess the effect of water inflows on the strength characteristics of the rocks composing the support pillars. The analysis and calculations of precipitation accumulation within the mine allotment and water inflows into the mine workings were performed and compared with actual data on mine waters. The samples of the most representative rocks of the deposit were collected and tested for dry and water-saturated compressive and tensile strength. The quantitative indicators of the changes in the strength characteristics of rocks due to water saturation were determined. It was found that the water saturation led to a decrease in the rock strength by up to 10–20%, especially for compressive strength values.